Acute sarcopenia changes following hospitalization: influence of pre-admission care dependency level. (9th August 2021) - De Spiegeleer, Anton; Kahya, Hasan; Sanchez-Rodriguez, Dolores; Piotrowicz, Karolina; Surquin, Murielle; Marco, Ester; Detremerie, Celine; Hussein, Dhurgham; Hope, Suzy; Dallmeier, Dhayana; Decker, Genia; Hrnciarikova, Dana; et al.
Abstract: Introduction: Hospitalization is associated with acute changes in sarcopenia status in older people, but the influencing factors are not fully understood. Pre-admission care dependency level as a risk factor has not yet been investigated. Objective: Evaluate if pre-admission care dependency level is an independent predictor of sarcopenia changes following hospitalization. Setting and subjects: Data came from the Sarcopenia 9+ EAMA Project, a European prospective multi-centre study. For this study, 227 hospitalised older people were included from four different hospitals in Belgium, Spain and Poland, between 18 February 2019 and 5 September 2020. Methods: Sarcopenia status at admission and discharge were calculated using a combined score (desirability value) based on muscle mass (calf circumference), strength (grip) and function (walking speed). Ratio of admission to discharge status was the outcome (desirability ratio; 1.00 meaning no difference). Predictor variable was the pre-admission care dependency level, classified into three groups: independent older people living at home, dependent older people living at home and older people living in a care home. Linear regression models were applied, considering potential confounders. Results: Mean desirability ratio for dependent older people living at home ('middle dependent group') was lower (0.89) compared to independent older people (0.98; regression coefficient −0.09 [95% CI −0.16, −0.02]) and care home patients (1.05; −0.16 [95% CI −0.01, −0.31]). Adjusting for potential confounders or using another statistical approach did not affect the main results. Conclusion: Dependent older people living at home were at higher risk of deterioration in sarcopenia status following hospitalization. In-depth studies investigating causes and potential interventions of these findings are needed.